The Association between Anxiety and Professionalism in Residents of ENT Specialist Training Program in the Faculty of Medicine, Gadjah Mada University, Indonesia - Budi Santosa; Carla Raymondalexas Marchira; Sumarni Sumarni; Bambang Udji Djoko Rianto; Irwan Supriyanto (Tabriz University of Medical Sciences, 2017)
Background: Professionalism has become a compulsory component of medical education, particularly due to the emergence of malpractice lawsuits. During specialist training programs, anxiety is one of the factors that affects education in professionalism. Anxiety is closely associated with stressors during training programs. The ear, nose and throat (ENT) specialist training program in the Faculty of Medicine Gadjah Mada University is known to be highly demanding with a heavy load of stressors. The broad area of competence and professionalism demand in ENT training made its residents prone to anxiety, which in turn affects their professionalism. In this study we measured professionalism and anxiety of residents in the ENT specialist training program and the association between them. Methods: This was a cross-sectional study. The subjects were active residents in the Department of Ear, Nose, and Throat, Faculty of Medicine, Gadjah Mada University who fulfilled the inclusion and exclusion criteria (n = 39). Professionalism was measured using the Resident Professionalism Inventory (RPI). Anxiety was measured using the Hamilton Anxiety Rating Scale (HARS). Data was coded and statistically analyzed using SPSS version 17. Statistical significance was defined as P < 0.05. Results: The prevalence of anxiety was very low. Most subjects reported insufficient professionalism (53.8%; 95% CI = 0.372-0.699). The results showed no association between anxiety and professionalism (P > 0.05). Conclusion: Anxiety was not associated with professionalism in ENT training program residents. Further study in other departments is required to confirm these results.